FORMATION OF SPIRITUAL EDUCATION IN STUDENTS THROUGH FOLKLORE: EXPLORING CULTURAL NARRATIVES AND MORAL VALUES - Kurolova Mokhirakhom Adkhamovna (Galaxy International Interdisciplinary Research Journal, 2024)
This scientific article examines the role of folklore in the formation of spiritual education in students. Folklore, comprising traditional tales, legends, myths, and proverbs, carries cultural narratives and moral values that contribute to students’ spiritual development. By exploring various folklore genres, this article highlights the significance of folklore in cultivating ethical awareness, empathy, cultural appreciation, and a sense of identity among students. Additionally, it explores instructional strategies and approaches for effectively integrating folklore into educational settings to foster spiritual growth and character development.